Safety and efficacy of topically administered netarsudil (Rhopressa™) in normal and glaucomatous dogs with ADAMTS10-open-angle glaucoma (ADAMTS10-OAG) - Leary, Kelly A. (Vet Ophthalmol, 2019)
OBJECTIVE: To evaluate safety and efficacy of topically administered 0.02% netarsudil ophthalmic solution (Rhopressa™; Aerie Pharmaceutical) in normal and glaucomatous dogs with ADAMTS10-open-angle glaucoma (ADAMTS10-OAG). ANIMALS STUDIED: Five normal and 5 glaucomatous Beagle dogs with ADAMTS10-OAG. PROCEDURES: In each dog, left or right eye was randomly selected for netarsudil treatment. Contralateral eyes were sham-treated with balanced salt solution (BSS). Following a 1-week baseline period, dogs were treated once daily (q24h) during week 2, and twice daily (q12h) during week 3; week 4 served as washout period. Efficacy was measured by diurnal intraocular pressure (IOP) and pupil diameter. Safety was assessed by routine ophthalmic examination, gonioscopy and pachymetry. Differences in least square means of quantitative outcome measures were compared between netarsudil and BSS sham treated eyes by linear Gaussian model. RESULTS: Baseline IOPs were 18.5±0.5mmHg (mean±SEM) in normal and 27.8±1.0 mmHg in OAG dogs. Even though mean IOPs were lower in netarsudil- vs. sham-treated eyes, the overall differences were neither significant nor clinically relevant, regardless of treatment frequency (q24h-normal: sham 16.4±1.1 mmHg vs. treatment 15.6±1.0 mmHg; q24hr-OAG: sham 25.8± 2.3 mmHg vs. treatment 25.7± 2.4 mmHg; q12hr-normal: sham 15.4±0.8 mmHg vs. treatment 14.4±0.8 mmHg; q12hr-OAG: sham 26.3±1.7 mmHg vs. treatment 25.4±1.8 mmHg). Netarsudil administration was well tolerated but resulted in significant, moderate to severe conjunctival hyperemia (p<0.001). CONCLUSIONS: Once or twice daily administration of netarsudil resulted in marginal and clinically irrelevant IOP decreases in normal and OAG-affected dogs. Except for conjunctival hyperemia, the drug was well tolerated.